The Influence of XBRL Adoption on Financial Reporting Timeliness: Evidence from Indonesian Banking Industry - Tri Utami Lestari; Kartika Pratiwi Putri; Meita Candra Devi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study examines the impact of eXtensible Business Reporting Language (XBRL) adoption on financial reporting timeliness. The population are banking companies listed on the Indonesian Stock Exchange (IDX) between 2015 and 2019. The samples are 38 Indonesian banks or 190 bank-year observations. Using logistic regression this study demonstrates the XBRL adoption positively affects financial reporting timeliness. The findings confirm that XBRL adoption benefit banks as it stimulates automation process, improves cost-effectiveness, fasten data collection, enhances data reliability and accuracy, and thus it may lead to better business decision-making. The positive signal provided by the adopters of XBRL will influence the decisions of shareholders, which in turn will lead to share ownership increase.